Modeling of polycarbonate and thermotropic liquid crystalline polymer blends - Yang, Yue Xiang (2008)
The liquid crystalline polymer (LCP) belongs to a class of new polymers which were developed for their high performance properties such as tensile strength and modulus. The excellent properties of a liquid crystalline polymer can be attributed to its capacity for in-situ fiber formation during melt processing. However, LCPs are expensive. To lower costs, polymer blends containing LCP are utilized. The possibilities of using LCP as processing aids and/or for reinforcement are being explored. It has been shown that small amounts of LCPs may significantly lower the melt viscosity of many flexible polymers, thus enhancing their processability. LCPs can be blended with many common thermoplastics, without changing the processing techniques normally used for them.